The Influence of Product Prices, Sales Promotion and Services on the Purchase Decision of Indihome Products at PT. Telkom Solo - Dicky Budi Kristianto; Adhita Maharani Dewi (ProBisnis : Jurnal Manajemen, 2023)
Digital development requires PT Telkom to continue to transform in meeting customer needs. One of its superior products is Indihome. Indihome is a wifi product. Wifi is needed by everyone in everyday life, which used to be only a secondary need is now changing to primier, without internet humans cannot move in the era of digitalization. Seeing this, researchers made a study on the influence of price variables, products and services on purchasing decisions. As a result, all of these variables have a simultaneous and partial effect on purchasing decisions.